Pengaruh Model Pembelajaran Kooperatif TGT Berbantuan Quizizz Paper Mode Terhadap Pemahaman Konsep Matematika Berdasarkan Kecerdasan Emosional Sebagai Variabel Moderasi - Salsabila, Dewi Ula; Assegaf Baalwi, Muhammad (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2025)
This study has two objectives, namely explaining the effect of the TGT cooperative learning model assisted by Quizizz Paper Mode on students' understanding of mathematical concepts, with emotional intelligence as a moderating variable, and describing the understanding of mathematical concepts in terms of emotional intelligence. This study uses a mixed method with an explanatory sequential mixed methods design. The quantitative approach uses a pre-experimental research type with a one-shot case study design, while the qualitative approach uses a descriptive method. The results of the study indicate a significant effect of the TGT cooperative learning model assisted by Quizizz Paper Mode on students' understanding of mathematical concepts. Emotional intelligence as a moderating variable also has a significant positive relationship with students' ability to understand mathematical concepts. Students with high emotional intelligence tend to have a stronger understanding of concepts, while students with moderate emotional intelligence show sufficient understanding although not yet in-depth.  Keywords : Emotional Intelligence, Understanding of Mathematical Concepts, Quizizz Paper Mode, TGT